Automated Visa Dispensation Application System to Maintain a Repository of Information about Visa Applicants - Saravanan, M; Vadivel, R (International Journal of Computer Sciences and Engineering, 2020)
Project "Online Visa Processing System" is an automated program. It describes the process of applying for a visa. There are many types of visas granted by the government such as H1-visa, Dependent visa. Obtaining a Visa, issuing a Visa is a very meaningful decision, and it is not a contestant. Each visa officer has a list of requirements for which an applicant is applying for a visa. If met, the applicant issues a visa. Otherwise, the applicant does not. It is how these requirements are met that make the visa decision look good. In this paper the proposed system is a web-based system, using one that can store all information in an efficient and efficient way. The system allows storing aggregated data that has the properties to insert, edit and delete data as needed. The program is useful for the organization's Human Resources department to track staff details and their visits abroad. The program is proposed to consist of the following modules: Study Director, Visa Performance Module, Onsite Communication Module and Reporting Module.